Respon sSeismik dan Mitigasi Likuifaksi pada Tanah Miring Menggunakan Strategi Penurunan Muka Air Tanah - Rinarebut Rayhansah; muhsiung Chang; Hsu-Jen Lin; Hamzah Fansuri Muhammad; Togani Cahyadi Upomo; Rini Kusumawardani (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Liquefaction-induced slope failure remains a critical geotechnical problem in seismic regions, particularly under saturated sloping ground conditions. This study investigates the effects of slope inclination and groundwater depth on liquefaction behavior using numerical simulation under seismic loading. Three slope configurations (i1–i3) and two groundwater conditions, W2 (3.84 m) and W3 (9 m), were analyzed to evaluate excess pore water pressure (EPP), seismic amplification, spectral response, and lateral deformation. Results show that steeper slopes and deeper groundwater conditions significantly modified soil dynamic behavior. Peak acceleration increased from 0.127 g under i1–W2 to 0.190 g under i3–W3, while the dominant spectral period shifted to T ? 1.443 s with maximum spectral acceleration reaching Sa,max ? 0.529 g. Groundwater lowering (GL) effectively reduced pore pressure generation and produced nearly drained conditions within the computational zone. However, the Encased Stone Column (ESC) system provided better performance in minimizing lateral deformation and liquefaction-induced flow displacement. These findings demonstrate that hydraulic control and reinforcement systems play complementary roles in improving the stability of liquefaction-prone sloping soils under earthquake loading.